Welfare Tendency Probability: A Study on Poor Households in Indonesia - Rachmawati, Lucky; Cahyono, Hendry; Azhar, Nur Azirah Zahida Binti Muhammad; Othman, Norashida; Shakil, Nurul Syifaa Mohd; Arisetyawan, Kukuh (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2024)
Research Originality: Poverty is an important issue in the discussion of economic development. The problem of household poverty in Indonesia is not enough to be analyzed at the macro level; it should also be analyzed in microeconomic settings. Research Objectives: This study uses secondary data sourced from the results of the Indonesian Family Life Survey (IFLS) surveys in 2007 and 2014 to determine the trends in household characteristics (social, economic, and demographic) and their influence on the level of welfare of poor households, the share of household spending inequality, and poverty alleviation strategies through a household-based policy approach in Indonesia.Research Methods: Meanwhile, the research method used is Multinomial Logistic Regression.Empirical Results: The results of the study found that the education level of the head of the household, place of residence, and household size contributed to the value of the opportunity of the household welfare position in each category. Meanwhile, Javanese have the highest level of inequality in terms of ethnic expenditure distribution and the lowest in terms of welfare.Implications: This study implies that the condition of the head of the family dramatically influences welfare at the household level.JEL Classification: C49, O11, Q01, R58